Adalimumab Induced or Provoked MS in Patient with Autoimmune Uveitis: A Case Report and Review of the Literature - Rana Alnasser Alsukhni; Ziena Jriekh; Yasmin Aboras (Case Reports in Medicine)
Anti-tumor necrosis factor α (anti-TNF-α) agents have been widely used in the field of autoimmune diseases and have proved decisive efficacy and relative safety. Data concerning their adverse effects has been lately describing central nervous system (CNS) demyelination process at escalating basis. Case Presentation. A 23-year-old male with autoimmune uveitis and a family history of multiple sclerosis (MS) developed two neurological attacks, after Adalimumab infusion, simultaneously with several cerebral lesions on magnetic resonance imaging (MRI). Hence the diagnosis of Adalimumab induced MS was suspected. Conclusion. This case is reported to tell physicians to be cautious when using anti-TNF-α in patients with family history of MS and to reconsider the risk of MS in patients with autoimmune diseases.